STUDI PENDAHULUAN PENGARUH PENERIMAAN DAN PENGELUARAN NEGARA TERHADAP IMBAL HASIL MISMATCH TREASURY BILLS - Joko Sumantri, M.M (JURNAL PAJAK INDONESIA, 2017)
The purpose of this preliminary study is to assist the Indonesian government and investors in predicting the effect of changes in state revenues and expenditures on yields on bonds to be issued under the name "mismatch treasury bills". The yield of treasury bills mismatch debt is proxied with 3-Month Indonesian Bond Yield indicator. By using linear regression analysis, state revenues and expenditure variables do not show a significant influence on the 3-Month Indonesian Bond Yield indicator.